Rancang Bangun Sistem Keamanan Kampus Politeknik Negeri Medan Berbasis IoT dengan Deteksi Gerakan dan Pengawasan Jarak Jauh - Nur Adilah (Jurnal Nasional Teknologi Komputer, 2025)
This research aims to design and build a security system at the Medan State Polytechnic Campus based on the Internet of Things (IoT) which is equipped with motion detection and remote surveillance features. The system is designed to improve campus security by utilizing sensor technology and internet connectivity that allows real-time monitoring. In this study, motion sensors were installed in strategic areas on campus to detect suspicious activity. The data from the sensor will be sent to the server and processed to provide notifications to users through the mobile application when unusual movements are detected. The system is also equipped with remotely accessible surveillance cameras, allowing users to monitor the situation on campus anytime and anywhere. Research methods include system design, hardware and software programming, and system testing to ensure its performance and reliability. The test results showed that the system could detect movement with high accuracy and send notifications in less than a second. The remote surveillance feature also works well, giving users direct access to view live video footage. The conclusion of this study is that the designed IoT-based security system is effective in improving the security of the Polmed Campus. It is hoped that this system can be widely applied in other educational institutions to support the safety of students and staff. This research also opens up opportunities for further development in IoT-based security technologies.